The analysis of the factors affecting household water demand in Mpumalanga, South Africa - van Huyssteen, Thomas (School of Economics, 2021)
Understanding the evolution of water demand is of paramount importance for countries that want to implement the correct water demand management strategies that aim at increasing water use efficiency. This paper analyses household water demand in the capital city of the Mpumalanga Province of South Africa, in order to develop a better understanding of residential water demand in developing country contexts. Using survey data from 526 households in the Mbombela Municipality of Mpumalanga, South Africa, we estimate the price and income elasticities of household water demand, and investigate the factors that drive water demand of households that are located in heterogenous income groups. Households in the study areas have the unique characteristic seen in developing countries of having access to several sources of water, such as tap, ground and rainwater, implying the possibility of substitution. We run different estimation strategies that range from OLS, 2SLS and instrumental variable approaches to identify the factors that influence urban water demand. The findings reflect that price and income elasticities vary across different household groups, with price elasticities ranging from -0.140 to -0.879 and income elasticities ranging from 0.172 to 0.628. Other statistically significant variables which drive household water consumption are household size, education level, use of water saving technologies, and the use of rainwater tanks and systems. A crucial finding in this study was that water saving technologies were revealed to reduce water consumption levels by between 28.3% to 43.4%, and we hence provide specific policy recommendations based upon this finding. Overall, the results from this study can contribute substantially towards the development of appropriate and sustainable water policy making in South Africa.